Preparation and evaluation of sublingual tablets of zolmitriptan - Prajapati, Shailesh T; Patel, Manoj V; Patel, Chhaganbhai N (International Journal of Pharmaceutical Investigation)
Aim: Zolmitriptan is a 5-HT receptor agonist (1B/1D). It is used in the acute treatment of migraine having low bioavailability about 40% orally due to hepatic first pass metabolism. The purpose of the present research was to formulate fast acting sublingual tablets of zolmitriptan. Materials and Methods: Sublingual tablets were prepared using ispaghula husk powder, gellan gum, sodium alginate as super disintegrating polymers and citric acid, tartaric acid and camphor as permeation enhancers by direct compressible technique and evaluated for weight variation, thickness, friability, content uniformity, hardness, disintegration time, wetting time, in-vitro drug release, in-vitro and ex-vivo permeation study. Stability study of optimized formulation was performed as per ICH (International Conference on Harmonisation) guideline. Results: The in-vitro disintegration time of the optimized formulation (D5) was 9 ± 2 s and all formulations showed 100% of dissolution within 6 ± 2 min. Formulation containing 4% of gellan gum (D5) showed highest disintegration and 2% of citric acid formulation (P3) showed highest permeation 88% within 30 min and ex-vivo permeation was 52% within 30 min. Optimized formulation was stable for 1 month during stability study as per ICH guideline. Conclusion: The sublingual tablet formulation gives better results using natural super disintegrant for fast onset of action.
Keywords: Ex-vivo permeation; natural super disintegrants; permeation enhancers; sublingual tablets; zolmitriptan